Computer informatization: factors, difficulties and challenges (Research, Society and Development, 2019)
This article aims to understand the main factors that lead to the business computerization, as well as the main difficulties and challenges that SMEs - Micro and Small Companies face in this process. For that purpose, a questionnaire was developed and applied to fifteen companies from the Middle Piracicaba - MG, encompassing companies from the municipalities of João Monlevade, Nova Era and Bela Vista de Minas. The questionnaire involved questions related to Information Technology and Information Systems - SI resources such as: human, hardware, software, data and network. The theoretical basis that supports the object of the study is the result of bibliographical research, where the concepts of Information Technology - IT, Information Systems - SI and Human Resources (human, hardware, software, data and network) are exposed. As results, it was identified that the main factor that led the MSEs to the computerization process was the fiscal obligation. However, it was also possible to identify that many MSEs perform computerization in order to improve information quality, reduce costs and modernize. Regarding the main challenges and difficulties involved in the process of business computerization, it was identified that the implementation of network infrastructure is the most complex and emblematic.